Effectiveness of Multicultural Snakes and Ladder Media in Developing Attitudes of Tolerance in Social Studies Subjects of Grade IV Elementary School - Hanifah, Fatimah Hurin; Laila Fatmawati (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning social studies in elementary schools often remains theoretical and lacks opportunities for students to engage directly with character values such as tolerance. This study investigates the effectiveness of multicultural snakes and ladders media in developing tolerance attitudes among fourth-grade students. The research employed a quantitative approach using a quasi-experimental one-group pretest-posttest design involving 30 Giwangan State Elementary School students. Data were collected through questionnaires and analyzed using SPSS 26. The results showed a significant improvement in students' tolerance, with the mean score increasing from 18.83 to 22.23 and a significance value of 0.000. This indicates that the media effectively supports cognitive understanding and character values' internalization through an interactive and engaging format. This research contributes to enriching character education innovation by demonstrating how game-based multicultural media can be a practical tool in fostering tolerance in elementary school settings.